Solar Sentry: Solar Power Module with Border Alert System for Fishing Vessel - Parvathi S.R; Adithyan M.S; Moufina S.S; Abhiram S.M; Salini Venugopal (International Journal of Robotics and Automation in Mechanics, 2024)
Fishermen are being caught and killed by the naval forces of the neighboring country, due to the lack of awareness about the ocean frontiers and advanced alert instruments in the boats. For this reason, maritime security has become a major concern of all coastal areas to protect the fishermen and provide assistance about sea frontiers via alerting, tracking, and monitoring of boat vessels. Thereby, a path-breaking technology of maritime border alert system using smart vessels is proposed; This technology fosters coast guard officials to effectively monitor fishermen and alert them if they sail inside the other country’s border. Additionally, the implementation of lite loads powered by solar modules offers sustainability and cost-effectiveness for the fishermen in trawlers. The proposed border alert system and light loads powered by solar modules are a combination of technology innovation and renewable energy integration. This solution enhances the safety, efficiency, and sustainability of trawler fishing operations, benefiting both fishermen and the marine ecosystem. This technology integrates a border warning system with a renewable energy module to supply independent electricity for essential vessel operations and ensure compliance with maritime border laws. The solar power module reduces reliance on conventional fuel-powered generators and decreases emissions by utilizing solar energy to power navigation lights, communication devices, and other critical systems aboard the ship. When a vessel approaches prohibited areas or enters foreign waters, the border alert system uses GPS and geofencing devices to monitor its location relative to maritime boundaries and send real-time notifications.
Keywords: GPS; GSM; LCD; PV array; pulse-width modulation (PWM)